Representações midiáticas e idealizações sobre juventude e consumo: os sentidos do discurso na Revista Veja - Andrade, Tiago Pereira (2011)
This research examines the discourse of news and the covers of the magazine Veja on the theme of youth and consumption. The corpus includes a selection of the articles of the the magazines, published in the first semester of 2009. We are interested in questioning the extent to which these media representations put into circulation ideas that contribute to reading idealized dichotomous surface or stigmatized in particular on young people and youth in general, identifying even the centrality of consumer culture in the production of these representations. The first chapter, which precedes the analysis of the material, is focused on discussions about journalism, magazines and media. The following chapter presents the analysis of the issues selected, and the last chapter will discuss the main thematizations on youth found in the articles. The analysis focuses on the discourse and logic of production of meaning adopted by the magazine for the construction of certain representations of young people and youth, and also will consider the recurring themes at the research. The criterion for the survey was to compose directly thematized (youth) or approaches the subject of questions related to it as juvenilization or technologies. The dissertation is prepared through a literature review and documentary analysis and sociological elements of the analysis of media discourse. The bibliographic database covers Mayra Rodrigues Gomes, Nilson Lage, Ciro Marcondes Filho, Juremir Machado da Silva, Rosana de Lima Soares, Rose de Melo Rocha, Silvia Borelli, Maria Celeste Mira, Gislene Silva, Cristina Ponte, Everardo Rocha, Edgar Morin, Martine Joly, Guy Debord, Pierre Bourdieu and others in the field of communication and sociology.